The hunter and her witch - Sullivan, Rachel (Bold Strokes Books, 2025)
"Hunter Sarah left her religious witch-hunting family behind for the freedom to be herself. Simplicity is her mantra now, as she lives and works alongside her found family of supernatural women. The day Sarah shows up at a witch's property to build a yoga studio, though, her mantra skips a beat. For witch Oriana, leaving her abusive ex was her first step toward a new life. Moving to Obsidian Falls and becoming a yoga instructor quickly followed. Her dismal romantic track record is proof she needs to focus on anything but love. But the moment she sets eyes on a member of the supernatural construction crew building her studio, she knows her heart didn't get the memo. When Oriana's ex shows up, and Sarah's inner Hunter responds, their painful pasts collide in a waterfall of revealed secrets and fears come to life. They must decide if their love is worth building, or better left behind."